Education for Sustainable Development in Southeast Asia: Focus on Initiatives in Indonesia - Noviya, Anis (PT. Anagata Sembagi Education, 2024)
Education plays a critical role in achieving the Sustainable Development Goals (SDGs), particularly in Southeast Asia, which is undergoing rapid social and economic transformation. This article explores education initiatives for sustainable development in Indonesia, highlighting efforts to improve access to and quality of education and their impact on social and environmental sustainability. The main focus is on innovative programs oriented towards strengthening local skills, increasing environmental awareness, and integrating SDG principles into educational curricula. By analyzing initiatives from various sectors, this article provides insights into the challenges and opportunities in implementing sustainable education in Indonesia and its relevance for Southeast Asia as a whole.